2006
DOI: 10.1111/j.1574-695x.2006.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

A new synbiotic,Lactobacillus caseisubsp.caseitogether with dextran, reduces murine and human allergic reaction

Abstract: We studied the development of atopic dermatitis-like skin lesions in NC/Nga mice and the allergic symptoms and blood patterns of healthy volunteers during the cedar (Cryptomeria japonica) pollen season in Japan following oral administration of a new synbiotic, Lactobacillus casei subsp. casei together with dextran. The combination of L. casei subsp. casei and dextran significantly decreased clinical skin severity scores and total immunoglobulin E levels in sera of NC/Nga mice that had developed picryl chloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…This synbiotic combination significantly decreased clinical skin severity scores induced by picryl chloride and total IgE levels in sera of NC/Nga mice. 61 Also, supplementation with KW3110 strain of lactic acid bacteria significantly attenuated the onset and exacerbation of atopic dermatitis-like skin lesions, accompanied by lower plasma IgE levels through its effects on IL-12 and IL-4 production in vitro. 62 Oral administration of Lactobacillus brevis significantly inhibited IgE production and ear swelling, and suppressed the development of dermatitis in a dose-dependent manner in atopic dermatitis model of NC/Nga mice.…”
Section: R E T R a C T E Dmentioning
confidence: 94%
“…This synbiotic combination significantly decreased clinical skin severity scores induced by picryl chloride and total IgE levels in sera of NC/Nga mice. 61 Also, supplementation with KW3110 strain of lactic acid bacteria significantly attenuated the onset and exacerbation of atopic dermatitis-like skin lesions, accompanied by lower plasma IgE levels through its effects on IL-12 and IL-4 production in vitro. 62 Oral administration of Lactobacillus brevis significantly inhibited IgE production and ear swelling, and suppressed the development of dermatitis in a dose-dependent manner in atopic dermatitis model of NC/Nga mice.…”
Section: R E T R a C T E Dmentioning
confidence: 94%
“…Despite this potential, however, there are few in vivo human or animal studies providing evidence that prebiotics can be used to support specific probiotic strains. Unfortunately, most synbiotic studies, including work in rats (44)(45)(46)(47)(48)(49), mice (50)(51)(52), pigs (53)(54)(55)(56)(57), chickens (58,59), and humans (60), did not employ strainspecific detection methods and therefore did not provide information on the potential synergism between pre-and probiotics. Of the in vivo studies that did discriminate the probiotic strain, most still did not demonstrate that in vivo performance could be enhanced by a prebiotic.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent atopic dermatitis, L. johnsonii should be administered early in the weaning period in NC mice [5]. Oral administration of symbiotic L. casei was effective in preventing atopic lesions induced by 2,4,6-trinitro-1-chlorobenzene when dextran was administered simultaneously [11]. Pagnini et al demonstrated that to prevent the onset of intestinal inflammation by local stimulation of epithelial innate immune responses, a probiotic mixture containing Streptococcus thermophilus, Bifidobacterium infantis, L. acidophilus, and Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Lactobacillus spp. administration has a limited effect in preventing or inhibiting the development of atopic dermatitis [5,11,12]. Bacillus subtilis is one of the bacteria used for probiotics, and it is commonly used as an effective probiotic for preventing enteric infections in both humans and animals [20].…”
mentioning
confidence: 99%